Diseño de un circuito integrado digital como detector de disparos de armas de fuego y motosierras, basado en correlación bitstream - Loría-Marín, Gabriel (Instituto Tecnológico de Costa Rica, 2016)
The design process of an audio signal detector is a process that comprehends several elds of electronic engineering. Such as handling audio signals with proper treatment, principles of digital signal processing (DSP) and signal correlation in order to create a proper signal detection system. This document describes the design process in FPGA of an acoustic signal detector for enviromental protection aplications. This mentioned detector works with correlation signal theory, and its veri cation is made with previously recorded sounds of reguns and chainsaws.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2016.
Keywords: DSP; Manejo; Señales; Ingienería electrónica; FPGA; Procesamiento digital de señales; Diseño; Tecnología; Almacenamiento de señales